Awareness of addict personality traits and their relationship with Attitudes towards addiction among a sample of university students in light of academic year and father education level variables - Badawy, Walaa Badawy Mohamed (Journal of Educational and Psychological Sciences, 2022)
The research aims to recognize the correlation between awareness of addict personality traits and Attitudes towards addiction among a sample of King Khalid University female students and to recognize the differences among the research sample in the light of (academic year and father education level) variables. Suitable tools were used to examine and evaluate the research variables that are: the scale of addict personality traits and the scale of Attitudes towards addiction (prepared by the researcher) after verifying their psychometric characteristics (properties) by using the correlative descriptive method with a sample consisting of (128) female students of king Khalid University, who were randomly selected from the stage of bachelor four years. Their ages range was (18 to 22) years with an average of 20,9 year,The results of statistical analysis showed the following: There is awareness of addict personality traits with its different dimensions with (71%) percentage. There are no positive tendencies for the female students towards addiction. There are no differences with a significant statistical indication on the scale of addict personality traits with its different dimensions according to (the different academic year and father education level) variables among a sample of king Khalid university female students. There are differences with statistically significant in negative tendencies towards addiction according to the variable of academic year in favor of the older and according to father education level. There is a revers correlation between the performance scores on the scale of addict personality traits with its different dimensions and the scale of Attitudes towards addiction among a sample of king Khalid University female students. The researcher made some recommendation about the necessity of guiding the educational institutions for paying to psychological sides and making best use of youth energy through different activities to help them avoid being a prey for addiction.